Art beyond the West the arts of Africa, India and Southeast Asia, China, Japan and Korea, the Pacific, and the Americas - Kampen-O'Riley, Michael (Laurence King Publishing, 2001)
Photographs and text profile the art traditions of Africa, India, Southeast Asia, China, Japan, Korea, the Pacific, and the Americas.